ESP Teachers’ Perspectives on Medical and Economic Students’ Profiles in Indonesian Higher Education: A Needs Based Analysis - Suharyanto, S; Setyabudi, Titis; Prasetyo, Ahmad; Lutfiyah, Luluk (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to identify the learner profiles of economics and medical students at a university in Indonesia. The goal is to use these profiles as a foundational reference for customizing English for Specific Purposes (ESP) programs to suit students' contextual and disciplinary needs. Methodology: A qualitative approach was employed in this study. Data were collected through semi-structured interviews conducted in three rounds, each lasting 30 minutes. The participants consisted of 12 ESP lecturers from higher education institutions in Indonesia. Results: The findings revealed that medical students generally have high English proficiency, are hardworking, diligent, highly motivated, well-mannered, active, and goal-oriented. In contrast, economics students tend to be passive, sociable, polite, less motivated, lower in English proficiency, and more dependent on contextual learning. Applications/Originality/Value: This research highlights the necessity of considering students’ distinct characteristics in the development and implementation of ESP programs. Tailoring instructional strategies based on student profiles can significantly enhance the effectiveness and relevance of ESP teaching in higher education contexts.